1998
DOI: 10.1001/jama.279.14.1083
|View full text |Cite
|
Sign up to set email alerts
|

Visual Processing Impairment and Risk of Motor Vehicle Crash Among Older Adults

Abstract: Context.-Motor vehicle crash risk in older drivers has been associated with visual acuity loss, but only weakly so, suggesting other factors contribute. The useful field of view is a measure that reflects decline in visual sensory function, slowed visual processing speed, and impaired visual attention skills. Objective.-To identify whether measures of visual processing ability, including the useful field of view test, are associated with crash involvement by older drivers. Design.-Prospective cohort study with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
531
6
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 716 publications
(570 citation statements)
references
References 35 publications
24
531
6
5
Order By: Relevance
“…Memory training outcomes were measured by verbal memory tasks: Hopkins Verbal Learning Test total of the 3 learning trials (Brandt, 1991), Rey Auditory-Verbal Learning Test total of the 5 learning trials (Rey, 1941), and the Rivermead Behavioral Memory Test immediate recall (Wilson et al, 1985). Speed of Processing training outcomes were measured using computer-based visual attention tasks, the Useful Field of View (Owsley et al, 1998), with the key dependent variable being the shortest display time required to achieve 80% correct response rate. Reasoning training outcomes were measured by tasks requiring the identification of patterns in letter and word series problems: Letter Series total correct (Thurstone & Thurstone, 1949), Letter Sets total correct (Ekstrom et al, 1976), and Word Series total correct (Gonda & Schaie, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Memory training outcomes were measured by verbal memory tasks: Hopkins Verbal Learning Test total of the 3 learning trials (Brandt, 1991), Rey Auditory-Verbal Learning Test total of the 5 learning trials (Rey, 1941), and the Rivermead Behavioral Memory Test immediate recall (Wilson et al, 1985). Speed of Processing training outcomes were measured using computer-based visual attention tasks, the Useful Field of View (Owsley et al, 1998), with the key dependent variable being the shortest display time required to achieve 80% correct response rate. Reasoning training outcomes were measured by tasks requiring the identification of patterns in letter and word series problems: Letter Series total correct (Thurstone & Thurstone, 1949), Letter Sets total correct (Ekstrom et al, 1976), and Word Series total correct (Gonda & Schaie, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Crossing an intersection requires divided attention among several pieces of information, perceiving and processing changes in the traffic situation, perceiving and processing signals and traffic signs, determining and executing a course of action (Braitman et al, 2007), and decision making under time pressure (Brouwer & Ponds, 1994). Attentional capacity deficits seem to be the key for their increased involvement in accidents (Owsley et al, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Though driving a vehicle is shown to be a highly visual dependent task, a number of studies have shown that there is no clear relationship between visual acuity and driving performance (Ball et al, 1993;Decina & Staplin, 1993;Gresset & Meyer, 1994;Hills, 1980;Ivers et al, 1999; Johansson et al, 1996;Marottoli et al, 1994;McCloskey et al, 1994;Owsley et al, 1998;Owsley et al, 1991;Shinar & Schieber, 1991). However, some other tasks such as reading road signs and avoiding obstacles in the roadway, are found to be affected by visual acuity loss (Higgins et al, 1998).…”
Section: Visual Acuity and Driving Performancementioning
confidence: 99%